Instilling Marriage Values Among Muslim Karo Adolescents: An Islamic Counseling Perspective - Rachmadillah, Laila; Muktarruddin, Muktarruddin (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2023)
The phenomenon of religious conversion driven by marriage is increasingly prevalent among adolescents and young adults. This issue is often influenced by several factors, including cultural attachment, environmental pressure, and parental preoccupation with work, which limits open communication and supervision of their children. However, the lack of consistent religious guidance from parents during childhood and adolescence emerges as a dominant factor influencing religious conversion for marital reasons. This study aims to explore how Karo Muslim families instill marital values in their adolescent children and to understand the role of religious guidance in shaping these values. The research employed a qualitative approach using observation, interviews, and documentation as data collection techniques. Participants included five Karo Muslim families with adolescent children, the Head of the Office of Religious Affairs (KUA), and religious leaders. The findings indicate that marital values are instilled by parents as children reach adolescence (baligh). Religious guidance is conveyed through advice, exemplary behavior, and parental supervision. However, the effectiveness of such guidance is often hindered by limited parental religious knowledge, strong adherence to cultural traditions, work-related busyness, and environmental influences. This study contributes to a deeper understanding of the intersection of family, religion, and culture in shaping adolescents’ perceptions of marriage and underscores the importance of continuous religious education within Muslim families.